Hubungan Paparan Sinar Matahari, Status Gizi, dan Asupan Makan terhadap Kadar Vitamin D Anak dan Remaja Penderita Diabetes Mellitus Tipe 1 - Inggita Kusumastuty; Dian Handayani; Harjoedi Adji Tjahjono; Elsa Permata Sari; Silvy Kartika Rahayuningtyas; Andanu Bima Saputra (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
Background: Previous research state the correlation between vitamin D deficiency and Type 1 diabetes. The deficiency of Vitamin D is caused by vitamin D intake, sunlight exposure, or nutritional status. Indonesia, as a tropical country, is close to the equator and receives sunlight all year long. Little research has been done on vitamin D levels in children and adolescents with Type 1 Diabetes in Indonesia.Objective: The study aims to determine the relationship among sunlight exposure, nutritional status, food intake, and vitamin D levels in children and adolescents with Type 1 Diabetes.Methods: The study design was cross-sectional with a sample size of 31 children and adolescents aged 5-19 years. Sunlight exposure data were collected using the Sun Exposure Questionnaire form, nutritional status o BMI/age data were using the WHO Anthro, food intake data were using the Semi-Quantitative Food Frequency Questioner, and vitamin D level data were using the ELISA method. Statistical analysis was conducted by using SPSS Version 21 with Pearson and Spearman correlation test.Results: All respondents showed vitamin D deficiency. Most respondents had low sunlight exposure and nutritional status in the normoweight category. The majority of respondents had good energy and protein intake, excess fat, low carbohydrates, and low vitamin D and calcium.Conclusion:There is a positive relationship between sunlight exposure and vitamin D level (p = 0.001, r = 0.627). However, there is no relationship among nutritional status, protein intake, fat, carbohydrates, vitamin D and calcium on the level of vitamin D (p = 0.409; p = 0.240; p = 0.311; p = 0.822; p = 0.231; 0.382).